2021
DOI: 10.1371/journal.pntd.0009086
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioimycosis and white individuals: Susceptibility and biogeographic aspects in an important endemic area in Brazil

Abstract: Paracoccidioidomycosis (PCM) is a neglected mycosis most commonly occurring in Latin America. The etiologic agents are thermo dimorphic fungi of the genus Paracoccidioides, and cause an important granulomatous response in affected tissues. The Botucatu Medical School, from São Paulo State University (UNESP), is a PCM study pole, located in São Paulo State Midwest region, which is classified as a hyperendemic area in the Southeast region in Brazil. This study aimed to perform a retrospective epidemiological, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
2
1
0
Order By: Relevance
“…This illness has a profound socioeconomic impact since it affects mostly rural male workers, 30–50 years old, who are the main providers, hindering their ability to work [ 34 ]. Our clinical and socio-demographic data corroborate with the known literature regarding PCM [ 4 , 32 ], showing that chronic form was more frequently presented in males, white individuals, smokers, and alcoholics, with a median of age superior to 50 years old, as already described; while acute form affects both genders, white individuals, non-alcoholics, non-smokers, and of younger age [ 32 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This illness has a profound socioeconomic impact since it affects mostly rural male workers, 30–50 years old, who are the main providers, hindering their ability to work [ 34 ]. Our clinical and socio-demographic data corroborate with the known literature regarding PCM [ 4 , 32 ], showing that chronic form was more frequently presented in males, white individuals, smokers, and alcoholics, with a median of age superior to 50 years old, as already described; while acute form affects both genders, white individuals, non-alcoholics, non-smokers, and of younger age [ 32 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 90%
“…It was identified that most of our patients are residents of the São Paulo State with a few cases from Paraná. The analysis of the area showed that where the patients lived, the place where they came from at the moment of the PCM diagnosis and treatment start, was predominantly concentrated in municipalities at São Paulo State central west region, around the city of Botucatu, corroborating the data published in 2021 [ 32 ].…”
Section: Resultssupporting
confidence: 78%
“…Other opportunistic infections should also be checked when treating patients with DMTs in Latin America, such as paracoccidioidomycosis, caused by Paracoccidioides brasiliensis, an endemic fungus in Latin America, which mainly affects the lungs. 143,144 Its treatment, which usually includes itraconazole, has been described in detail. 145 In summary, post-marketing data and real-world evidence available in the Latin American population do not differ from results of international clinical trials.…”
Section: Pregnant Women With Msmentioning
confidence: 99%